1984
DOI: 10.1042/bj2230229
|View full text |Cite
|
Sign up to set email alerts
|

Release of Ca2+ from a non-mitochondrial store site in peritoneal macrophages treated with saponin by inositol 1,4,5-trisphosphate

Abstract: The effects of inositol 1,4,5-trisphosphate, prepared from human erythrocyte ghosts, on Ca2+ release from intracellular store sites were studied in saponin-treated guinea pig peritoneal macrophages. Micromolar concentrations of inositol 1,4,5-trisphosphate released Ca2+ within 1 min from store sites which had accumulated Ca2+ in the presence of 10 mM-NaN3. In the presence of 10 mM-NaN3, the Ca2+ accumulated in the presence of oxalate was seen in the endoplasmic reticulum of saponin-treated macrophages by elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(48 citation statements)
references
References 20 publications
2
45
1
Order By: Relevance
“…Compared with the IP3R-labelled ER domain, the 3F3A ER domain shows increased dissociation from mitochondria in RAS-transformed NIH-3T3 cells relative to nontransformed NIH-3T3 cells. IP3R gating occurs at a [Ca 2+ ] cyt of 200-300 nM (Bezprozvanny et al, 1991;Hirata et al, 1984;Iino, 1990). This is slightly higher than reported here for mitochondrial dissociation of the 3F3A SER domain (100-200 nM) but sufficient for increased clustering of IP3R in the ER adjacent to mitochondria (Shuai and Jung, 2003;Wilson et al, 1998).…”
Section: Regulation Of Ser Tubule-mitochondria Interactioncontrasting
confidence: 40%
“…Compared with the IP3R-labelled ER domain, the 3F3A ER domain shows increased dissociation from mitochondria in RAS-transformed NIH-3T3 cells relative to nontransformed NIH-3T3 cells. IP3R gating occurs at a [Ca 2+ ] cyt of 200-300 nM (Bezprozvanny et al, 1991;Hirata et al, 1984;Iino, 1990). This is slightly higher than reported here for mitochondrial dissociation of the 3F3A SER domain (100-200 nM) but sufficient for increased clustering of IP3R in the ER adjacent to mitochondria (Shuai and Jung, 2003;Wilson et al, 1998).…”
Section: Regulation Of Ser Tubule-mitochondria Interactioncontrasting
confidence: 40%
“…Indeed, the notion that IP 3 mediates Ca 2+ release in the heart is not new, and has been established by studies spanning the last two decades. The very earliest studies on cardiac IP 3 signaling found evidence for functional IP 3 Rs capable of releasing Ca 2+ from the SR [47][48][49][50][51]. However, compared with Ca 2+ -induced Ca 2+ release through RyRs, though, the IP 3 -induced Ca 2+ release was slow and small.…”
Section: The Dilemma Of Cardiac Ip 3 Receptors: Lost In An Ocean Of Rmentioning
confidence: 99%
“…
(2,14,25). IP3 may be phosphorylated to form other inositol phosphates (19) or hydrolyzed in a 3-step dephosphorylation into inositol and Pi by specific phosphatases (3).

Although very little is known about signal transduction in higher plant cells, calcium has become recognized as a key regulator of plant metabolism (11,12,18,23,26).

…”
mentioning
confidence: 99%